BEDAH ULANG PERBANKAN KONVENSIONAL VERSUS PERBANKAN SYARI’AH DALAM REALITAS SOSIOLOGIS - La Samsu (TAHKIM, 2017)
Islamic banking as part of the financial structure of Islam played a role in economic development activities. However, there are many who consider the Islamic banking system is the same as the conventional banking system. It was only based on the addition of loans to customer deposits of Islamic banks and Islamic banks. When examined in depth the wrong turns that view because, although the similarities between Islamic banking and conventional banking, but both have a difference of principle. Islamic banking business activities based on Islamic principles. Services in payment traffic between banks and other parties to deposit funds or financing business activities, or other activities, among others the principle of mudaraba, musharaka, murabaha and ijarah. While conventional banks provide services in payment traffic, with the principle of determination of the interest as the price, both for product savings and loan products (credit) granted by certain interest rate. For services other banks, the banks implement a cost-based fee. Keywords: Islamic banking, conventional banking, sociological